166k views
16 votes
(Show your work) Factor out the GCF: 6x3y2z4 - 7x2y5z

User Halostack
by
5.8k points

1 Answer

9 votes

Answer:

x²y²z is the Greatest Common Factor

Therefore,

6x³y²z⁴ - 7x²y⁵z = x²y²z (6xz³ - 7y³)

Explanation:

Given the expression

6x³y²z⁴ - 7x²y⁵z

The first step is to factor out the greatest common factor from each term

6x³y²z⁴ = 2 · 3 · 6 · x · x · x· y · y · z · z · z · z

7x²y⁵z = 7 · x · x · y · y · y· y · y · z

So

G.C.F = x · x . y · y . z

G.C.F = x²y²z

Thus, x²y²z is the Greatest Common Factor

Therefore,

6x³y²z⁴ - 7x²y⁵z = x²y²z (6xz³ - 7y³)

User Degratnik
by
5.4k points